Future Making: Towards a Practice Perspective - Wenzel, Matthias; Cabantous, Laure; Koch, Jochen (Journal of management studies, 2025)
Management scholars are increasingly interested in ‘future making’, observing and theorizing how organizational actors produce and enact the yet‐to‐come. However, the rapid growth of the conversation runs the risk of emptying the notion of future making, calling into question its meaning and relevance. In response to these concerns, our Point is that there is value in understanding future making from a practice perspective. A practice perspective, we argue, is empirically sufficiently open to account for the plurality and open‐endedness of futures and future making amidst the continual emergence of interrelated crises, large‐scale challenges, and intractable technologies. Thus, it reinforces the relevance of research on future making as a central part of contemporary organizational life. At the same time, the four practice‐based dimensions elaborated in this Point provide sufficient conceptual specificity to discern what counts as future making and what does not, thereby providing solid ground for cumulative theory‐building and research in this area. Our Point extends research on future making in management studies by substantiating the relevance of examining and theorizing future making, and by articulating and clarifying a practice perspective on future making that directs scholarly attention to important areas for future research.